2013
DOI: 10.1371/journal.pone.0056249
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Bacterial Pneumonia Risk in Patients with Treated HIV Infection: A Case-Control Study

Abstract: BackgroundDespite advances in HIV treatment, bacterial pneumonia continues to cause considerable morbidity and mortality in patients with HIV infection. Studies of biomarker associations with bacterial pneumonia risk in treated HIV-infected patients do not currently exist.MethodsWe performed a nested, matched, case-control study among participants randomized to continuous combination antiretroviral therapy (cART) in the Strategies for Management of Antiretroviral Therapy trial. Patients who developed bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…Such elevations in HIV-infected patients predict poor clinical outcomes, including bacterial pneumonia 36 and death 37 . Similar elevations have been observed in non-HIV COPD cohorts 38 and such elevations similarly predict poor non-HIV COPD outcomes such as exacerbations of disease 39 (which are often triggered by bacterial infections) and death 40 .…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Such elevations in HIV-infected patients predict poor clinical outcomes, including bacterial pneumonia 36 and death 37 . Similar elevations have been observed in non-HIV COPD cohorts 38 and such elevations similarly predict poor non-HIV COPD outcomes such as exacerbations of disease 39 (which are often triggered by bacterial infections) and death 40 .…”
Section: Text Of Reviewmentioning
confidence: 99%
“…The primary article for the START study reported a reduced risk of bacterial infectious disorder events and incidence of tuberculosis in the immediate-initiation group. Characterisation of the effect of early ART on the incidence of bacterial infections is important because these events are common in people living with HIV 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…While there is now a broad consensus that immune activation and inflammation persist in the majority of HIV-infected individuals maintaining long-term ART-mediated viral suppression – even in those that restore normal CD4+ T cell counts [2326], and that immune activation and inflammatory markers strongly predict morbidity and mortality and even frailty in this setting [2737], the degree to which inflammation is a direct cause of morbidity and mortality in this setting remains controversial. A prominent role of the inflammatory state in explaining the excess morbidity and mortality observed in treated HIV infection is supported by several observations.…”
Section: Relative Importance Of Inflammation As a Target For Intervenmentioning
confidence: 99%
“…Two recent studies determined that soluble markers of innate immune activation predicted non-AIDS events and mortality during ART-mediated viral suppression much more strongly than T cell activation and senescence [64, 65]. These studies suggest that innate immune activation may be a more relevant target for interventions than T cell activation or senescence, but there remains a myriad of potential innate immunologic pathways that could be targeted [2737]. …”
Section: Identifying the Most Appropriate Targets For Interventionsmentioning
confidence: 99%